JOIN VENTURE AGREEMENT IN THE JOIN VENTURE COMPANY - Sri Purwaningsih, Pujiyono, Sri Walny Rahayu (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Join Venture Aqreement (JVA) is one procedure that must be taken in the establishment of PT. Join Venture Company. This agreement contains the parties' will in more detail, decomposing and complete what has been stated in a Memorandum of Understanding (MOU) but fundamental. Whereas in the MOU there is outlined the basic points of the desired problem can be further realized. For example, how much capital is part of each party and the ratio (Equity or Capital Participation Ratio).